Metadata on the Internet - Sequeira Ortiz, Deyanira (1996)
On the Internet, metadata are data about the information resources available on the Internet. Librarians have created metadata for centuries by building bibliographic records using classifications and cataloguing rules. Network users have decided to learn from librarians how to organize information.